1986
DOI: 10.1111/j.1471-0528.1986.tb07926.x
|View full text |Cite
|
Sign up to set email alerts
|

Episiotomy repair—immediate and long‐term sequelae. A prospective randomized study of three different methods of repair

Abstract: Three methods of episiotomy repair were randomly assigned after 900 consecutive deliveries. The three procedures were: (1) continuous No. 00-plain catgut in the vagina; No. 00-plain catgut interrupted stiches in the perineal muscles and fascia, and No. 00-nylon interrupted stiches in the skin. (2) The same technique as in (l), but with No. 0-polyglycolic acid (Dexon) in all layers. (3) The suture material as in (2), but used with a subcuticular technique. The women treated with method 3 reported statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Episiotomy (Ep) is the most common operative procedure during delivery (Pritchard & McDonald 1980, Reading et al 1982, Thacker & Banta 1983. A high frequency of postepisiotomy discomfort and pain has been reported in several studies (Buchan & Nicholls 1980, Kitzinger & Walters 1981Reading et al 1982, Thacker & Banta 1983, Sleep et al 1984, Isager-Sally et al 1986). There are many studies about Ep which document undesirable side effects with almost no evidence that the operation has any benefits.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Episiotomy (Ep) is the most common operative procedure during delivery (Pritchard & McDonald 1980, Reading et al 1982, Thacker & Banta 1983. A high frequency of postepisiotomy discomfort and pain has been reported in several studies (Buchan & Nicholls 1980, Kitzinger & Walters 1981Reading et al 1982, Thacker & Banta 1983, Sleep et al 1984, Isager-Sally et al 1986). There are many studies about Ep which document undesirable side effects with almost no evidence that the operation has any benefits.…”
Section: Introductionmentioning
confidence: 72%
“…The fact that E p had significantly more sutures than ST (Table 111) might have a negative effect on both healing and comfort, due to the long dissolving time of Dexon. According to Willmoth (1980) andIsager et al (1986) Dexon takes three to six weeks to disappear and Buchan & Nicolls (1980) claim that it can take as long as 60-90 days. Even Reading et al (1982) state that a large number of stitches increase the pain.…”
Section: Nsmentioning
confidence: 99%
“…However, although there is a great preference for one technique, there are only a few clinical trials that compare the effects of different suture techniques on the magnitude of maternal morbidity associated with repair of the perineum. [11][12][13] Fleming 14 published his experience in the use of the subcutaneous suture technique in repairing the skin and suggested that this technique was associated with a lower degree of pain in the perineum compared with other more traditional methods of suture.…”
Section: Discussionmentioning
confidence: 99%
“…dyspareunia. Several research studies 1,4,5,[7][8][9][10][11]12 have reported that 62-88% of women resume intercourse by 8-12 weeks postpartum. However, 17-23% continue to experience superficial dyspareunia at three months after delivery and 10-14% at 12 months.…”
Section: Dyspareunia Following Childbirth Christine Kettle Khaled Ismentioning
confidence: 99%
“…The effect of suture materials and methods used for repair of episiotomies and perineal tears following delivery has been assessed in several clinical trials with conflicting results relating to reported rates of dyspareunia. 4,7,[10][11]18 Implementation of strategies to reduce assisted vaginal deliveries using the Ventouse vacuum extractor as the instrument of choice rather than forceps, reducing episiotomy rate and improving perineal repair techniques, will probably help in decreasing the extent of postpartum sexual morbidity experienced by women.…”
Section: Perineal Injurymentioning
confidence: 99%